Physical, Thermal and Water-Sorption Properties of Passion Fruit Seeds - Souza, Silvio J. Ferreira de [UNESP]; Vaquiro, Henry A.; Villa-Velez, Harvey A. [UNESP]; Polachini, Tiago C. [UNESP]; Telis-Romero, Javier [UNESP] (Walter De Gruyter Gmbh, 2014)
Passion fruit seeds are an important by-product of the juice industry. In this study, physical, thermal and water-sorption properties of passion fruit (Passiflora edulis Sims f. flavicarpa Degener) seeds were determined. The knowledge of such properties is useful to design equipment or operations for storage or processing purposes. The physical properties of bulk density, particle density and bulk porosity, and the thermal properties of conductivity, diffusivity and specific heat were determined between water and mass fractions of 0.126 and 0.493. The thermal properties were determined for packed beds of seeds (effective properties), by means of which the thermal properties of the seeds (particle properties) were estimated. Different empirical models were evaluated for modeling the physical and thermal properties as function of moisture content. Physical and thermal properties were successfully described by a second-order polynomial, except by the specific heat which was described by a second-order logarithmic relationship. The isosteric heat, the differential entropy and the Gibbs free energy of water sorption were estimated using the Henderson model, which best fitted the experimental desorption isotherms at temperatures between 30 degrees C and 70 degrees C and relative humidities between 2% and 90%.
Keywords: physical properties; thermal properties; thermodynamic properties; Passiflora edulis; modeling